Community-Based Health Education on Healthy Foods to Reduce Blood Pressure among Hypertensive Patients in the Community - Israfil Israfil; Ni Luh Putu Inca Buntari Agustini; I Gede Putu Darma Suyasa; Ni Luh Dwi Indrayani; I Ketut Swarjana; Ni Kadek Sriasih; Ganyanee Nooiad; I Gusti Agung Yogi RS; I Nyoman Tripayana; I Gusti Agung Tresna Wicaksana (Ahmar Metakarya: Jurnal Pengabdian Masyarakat, 2026)
Hypertension is one of the non-communicable diseases whose prevalence continues to increase and remains a major risk factor for cardiovascular disease. The management of hypertension does not rely solely on pharmacological therapy but also requires non-pharmacological interventions, such as adopting a healthy diet rich in fruits and vegetables and low in salt. However, public knowledge regarding types of foods that effectively help lower blood pressure remains limited, particularly in rural areas. This community service program (PKM) aimed to provide education on healthy foods that can reduce blood pressure as a form of non-pharmacological therapy for patients with hypertension in the community. The activity employed the Preparation, Action, Reflection, and Evaluation (PARE) approach and was conducted in Melinggih Village, Gianyar Regency, Bali Province, involving 29 participants with hypertension. The program began with a pre-test, followed by health education sessions supported by visual educational media, consultations, discussions, and question-and-answer sessions, and concluded with a post-test evaluation. The results showed that the proportion of participants with good knowledge increased from 34.5% before the intervention to 100% after the implementation of the program. The Wilcoxon test results indicated Z = -4.300; p = 0.001, demonstrating a statistically significant difference in participants’ knowledge levels before and after the activity. The success of the program was supported by lecture methods, consultations, and interactive discussions conducted bilingually (Indonesian and Balinese), as well as the use of colorful leaflets illustrating vegetables and fruits beneficial in lowering blood pressure. Thus, this community-based educational intervention proved effective in improving community knowledge and awareness regarding healthy food choices for hypertension management.